Pelaporan Pajak Tahunan Orang Pribadi: Analisis Peran Dalam Mengoptimalkan Penggunaan Sistem E-Filing Di Masyarakat - Eka Satria Wibawa; Muksan Junaidi; Dhevi Dadi Kusumaningtyas (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Annual tax reporting is an obligation for every individual who meets the specified requirements. The use of e-filing systems in the tax reporting process has become more common in today's modern society. This study aims to analyze the role played in optimizing the use of e-filing systems in an effort to increase tax compliance among individuals. Qualitative research methods were used through interviews and observations of individuals involved in using this system. The results of the analysis show that understanding the role played in optimizing the use of e-filing systems can help increase the efficiency and effectiveness of individual tax reporting